Root and shoot transcriptome analysis of two ecotypes of Noccaea caerulescens uncovers the role of NcNramp1 in Cd hyperaccumulation. (2nd April 2014) - Milner, Matthew J.; Mitani‐Ueno, Namiki; Yamaji, Naoki; Yokosho, Kengo; Craft, Eric; Fei, Zhangjun; Ebbs, Stephen; Clemencia Zambrano, M.; Ma, Jian Feng; Kochian, Leon V.
Summary The Zn/Cd hyperaccumulator, Noccaea caerulescens, has been studied extensively for its ability to accumulate high levels of Zn and Cd in its leaves. Previous studies have indicated that the Zn and Cd hyperaccumulation trait exhibited by this species involves different transport and tolerance mechanisms. It has also been well documented that certain ecotypes of N. caerulescens are much better Cd hyperaccumulators than others. However, there does not seem to be much ecotypic variation for Zn hyperaccumulation in N. caerulescens. In this study we employed a comparative transcriptomics approach to look at root and shoot gene expression in Ganges and Prayon plants in response to Cd stress to identify transporter genes that were more highly expressed in either the roots or shoots of the superior Cd accumulator, Ganges. Comparison of the transcriptomes from the two ecotypes of Noccaea caerulescens identified a number of genes that encoded metal transporters that were more highly expressed in the Ganges ecotype in response to Cd stress. Characterization of one of these transporters, NcNramp1, showed that it is involved in the influx of Cd across the endodermal plasma membrane and thus may play a key role in Cd flux into the stele and root‐to‐shoot Cd transport. NcNramp1 may be one of the main transporters involved in Cd hyperaccumulation in N. caerulescens and copy number variation appears to be the main reason for high NcNramp1 gene expression underlying the increased Cd accumulation in the Ganges ecotype.